Korelasi antara perhatian orang tua dan disiplin belajar terhadap motivasi belajar matematika mahasiswa - Fitriani, Fitriani; Elisa, Elisa; Rossiah, Rossiah; Lubis, Rahmat Sholih (Journal of Didactic Mathematics, 2024)
This study investigates the correlation between parental attention and study discipline with students' motivation to learn mathematics. The research employs a descriptive quantitative approach, utilizing path analysis, which includes correlation analysis followed by regression analysis. The results reveal a correlation coefficient of 0.844 between parental attention, study discipline, and student's motivation to learn mathematics, categorizing it as "very strong." Furthermore, the multiple linear regression analysis yielded the following regression equation: . The study concludes a significant correlation between parental attention, study discipline, and students' motivation to learn mathematics. Additionally, the findings suggest that the greater the parental attention and study discipline, the higher the students' motivation to learn mathematics, and vice versa.